UNDERSTANDING THE IMPORTANCE OF PLANNING AND URBAN DESIG –Creating Theoretical Base For The Research On Composition Of Cities (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Kevin Lynch saw urban design as a branch of architecture; Michael South-worth on the other hand thought urban design as a branch of urban planning. Urban design is the process of shaping the man-made environment to fulfill the needs and values of a community in cities, towns and villages. The public spaces around buildings are as much of a concern in urban design as buildings themselves. There is a trend to formulate urban design as the interface between architecture and town planning, or the gap between them. Urban planning primarily concerned with the allocation of resources according to projections of future need. With planning tools and methodologies, land use as a distribution of resources and parceling out land for zoning purposes etc. are done at primary stage. The knowledge of planning becomes essential for all other interdisciplinary professions and the same is taught as the basic tool. Urban design makes imaged spatial arrangements like green lung spaces, housing typologies and boulevard, planning makes provision for spatial arrangements of known forms like land use, infrastructure, transport and built vs. open spaces therefore planning makes urban design focus on practical aspects more importantly before the three dimensional aspects are looked into.